A comprehensive cost-effectiveness analysis of control of maize streak virus disease with Holling’s Type II predation form and standard incidence - Seidu, Baba; Asamoah, Joshua Kiddy K.; Wiah, Eric Neebo; Ackora-Prah, Joseph (Elsevier, 2024)
This article is published by Elsevier 2022 and is also available at https://doi.org/10.1016/j.rinp.2022.105862